Reidentification of Redshifts of SDSS Galaxies Overlapped with Galactic Objects - Masafumi Yagi; Masanori Iye; Hideya Fukumoto (The Astronomical Journal)
This work presents a catalog of reidentified redshifts of 853 galaxies for which the redshifts of overlapping foreground objects were registered in the Sloan Digital Sky Survey (SDSS) DR16 Database. We examined SDSS DR16 spectra of the candidates contaminated by foreground Galactic stars and reidentified their galaxy redshift features, such as H α and other emission lines or absorption lines. Comparisons of redshifts measured at neighboring fibers, previous SDSS fits, and other published literature showed that our reidentification of redshift would be accurate to within 0.001. For the redshift range, 0 <  z  < 0.35, at least 0.1% of galaxies overlap with Galactic stars, and SDSS DR16 assigns the redshift of the foreground object, not the galaxies.